A review on mixed mode fracture of metals. (August 2020) - Wang, Yanlin; Wang, Weigang; Zhang, Bohua; Li, Chun-Qing
Highlights: Mixed mode fracture parameters, criteria and tests of metals are critically reviewed. A comprehensive review of effects of Mode II or Mode III on fracture resistance. Further verification tests of EPFM-based mixed mode fracture criteria are required. Mixed-mode fracture tests of metals under plane strain condition are required. Abstract: Mode I fracture mechanics has been relatively mature but mixed mode fracture mechanics continues to present challenges, in particular for ductile materials under multiaxial stresses. Since most engineering materials, e.g., metals, exhibit elasto-plastic or ductile behaviour and are subjected to inclined cracks and/or multiaxial loading, there is a well justified need to establish a solid understanding of their fracture behaviour under mixed modes. The intention of this paper is to critically review mixed mode fracture criteria for predicting the crack propagation in metals. Experimental methods for determining the fracture toughness under different mode mixities are reviewed and discussed. More importantly, research gaps in current studies are identified and further research needs are proposed. Through this review, it is found that the mixed mode fracture criteria need to be based on elasto-plastic fracture mechanics to account for large plastic deformation, and that for ductile metals, the addition of Mode II or Mode III loading can lead to a remarkable decrease of total fracture toughness of the metal, whilst the total fracture toughness of less ductile metals is insensitive to the addition of Mode II or Mode III loading. This review can contribute to the development of advanced mixed mode fracture criteria and testing methods for ductile metals.